2011
DOI: 10.3144/expresspolymlett.2011.78
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial adhesion of nanoparticles in polymer blends by intrinsic fluorescence spectra

Abstract: Abstract.Intrinsic fluorescence was applied to quantitatively describe the interfacial adhesion of nanoparticles in polystyrene/poly(vinyl methyl ether) (PS/PVME) blends. Due to the aggregation of aromatic rings on PS chains, the temperature dependence of excimer fluorescence intensity (I 324 ) showed the high sensitivity to the phase separation process. Consistent with Ginzburg thermodynamic model, it was found that the addition of spherical hydrophilic nanoparticles shifted the phase separation temperature t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…Meanwhile, the emission peak intensity of poly (BImBHCS-X) (X" = Br", BF 4 ", PF 6 " and TFSI") was much stronger than that of PBBHCS. This indicated that the counter-anions inserted into the polymer samples hindered the strong high-ordering packing of the side chain biphenyl mesogens, which resulted in the absence of fluorescence quenching [66][67][68][69]. The fluorescence emission spectra results were consistent with the previous results describing the structures of the MCSC-ILCPs poly(BImBHCS-X).…”
Section: The Photophysical Properties Of Mcsc-ilcps Poly(bimbhcs-x)supporting
confidence: 81%
“…Meanwhile, the emission peak intensity of poly (BImBHCS-X) (X" = Br", BF 4 ", PF 6 " and TFSI") was much stronger than that of PBBHCS. This indicated that the counter-anions inserted into the polymer samples hindered the strong high-ordering packing of the side chain biphenyl mesogens, which resulted in the absence of fluorescence quenching [66][67][68][69]. The fluorescence emission spectra results were consistent with the previous results describing the structures of the MCSC-ILCPs poly(BImBHCS-X).…”
Section: The Photophysical Properties Of Mcsc-ilcps Poly(bimbhcs-x)supporting
confidence: 81%
“…Recently it has been suggested that the use of NPs could be an alternative to 'compatibilising' immiscible polymer pairs 31 because they affect phase separation behaviour. 32 It was supposed that the silver NPs will have a double role as an antimicrobial agent and they will improve the compatibility of PLA with plasticisers and biological polymers (HC).…”
Section: Introductionmentioning
confidence: 99%